Monetary policy transmission: Balance sheet channel and investment behavior of firms in Pakistan - Amir Rafique; Muhammad Umer Quddoos; Shujat Ali; Faheem Aslam; Muneeb Ahmad (Economic Journal of Emerging Markets, 2021)
Purpose - This study investigates the relevance of the balance sheet channel of monetary policy transmission concerning non-financial firms at the Pakistan Stock Exchange (PSX), a firm-level data.Methods - This paper estimates a family of panel data regression models and constructs a dummy variable for monetary policy tightness.Findings - The result indicates a positive relationship between cash flows and investment during periods of monetary tightness. The impact on cash flows is visibly more pronounced than that of the quantitative effect of an increase in capital cost, which gives rise to a balance sheet channel. Three financial constraints, namely size, leverage, and dividend policy, are used to segregate firms into financially constrained and unconstrained firms.Implication - The results highlight the balance sheet channel impact on smaller firms' cash. The cash flows of highly leveraged firms were impacted more during the tight monetary policy periods and thereby were more prone to decline in investments. Results on constraints of dividend policy are, however, inconclusive.Originality - The paper contributes to the literature by investigating the relevance of the balance sheet channel of monetary policy transmission concerning non-financial firms using firm-level data. It also contributes to the literature by constructing a dummy variable to measure monetary policy tightness.